Errors in Judicial Decisions - Joep Sonnemans; Frans van Dijk (Tinbergen Institute, 2008)
In criminal cases the task of the judge is to transform the uncertainty about the facts into the certainty of the verdict. In this experiment we examine the relationship between evidence of which the strength is known, subjective probability of guilt and verdict for abstract cases. We look at two situations: (1) all evidence is given and (2) evidence can be acquired. Roughly half of the participants do not base their decision on a subjective belief of the probability of guilt. The others underestimate in general the probability of guilt, but this is more than compensated by a tendency to convict at too low probability of guilt. In the situation where evidence can be acquired, participants do not acquire enough evidence.
Keywords: C91; D81; K4; 330; Decision under uncertainty; judicial decisions; experiment; Kriminalität; Entscheidung bei Unsicherheit; Straftäter; Test; Theorie